Integrated Formal Methods : 14th International Conference, IFM 2018, Maynooth, Ireland, September 5-7, 2018, Proceedings /: 14th International Conference, IFM 2018, Maynooth, Ireland, September 5-7, 2018, Proceedings. (2018) - Unknown
No abstract available